Chemical Head Loss Measurements on Multi-Constituent Debris Beds in Small-Scale Experiments. (2nd December 2018) - Ali, Amir; Howe, Kerry J.; Blandford, Edward D.
Abstract: A series of experiments on vertical head loss modules or columns to measure conventional and chemical head loss was carried out to support the resolution of Generic Safety Issue 191 for the Vogtle nuclear power plant (NPP). The head loss (conventional and chemical) was measured on multi-constituent fibrous debris beds of different particulate-to-fiber ratios (η). The debris beds were generated on a horizontal screen following the new procedure developed at the University of New Mexico and are summarized herein. The generated debris beds have been shown to produce repeatable and stable conventional head loss (CHL) and have the ability to detect chemical surrogates. Prototypical Vogtle NPP containment debris materials were used to form three different particulate-to-fiber–ratio (η) debris beds: 6.89 (thin bed), 2 (intermediate bed), and 1.15 (thick bed). The particulates were presented as 90% epoxy paint, 5% inorganic zinc, and 5% latent debris dirt by mass. The obtained results show that the measured CHL increased as the particulate mass increased in the debris beds. The average measured CHL values were 9.37, 6.4, and 5.66 H2 O '' for η = 1.15, 2, and 6.89 debris beds, respectively. The debris beds with η = 2 and 1.15 were selected for the chemical head loss experiments. Standard aluminum (Al) chemical precipitates with specific batches were introduced to the head loss columns, and chemical head loss was measured. Precipitates prepared following the WCAP-16530-NP-A procedure [Lane et al., WCAP-16530-NP-A, "Evaluation of Post-Accident Chemical Effects in Containment Sump Fluids to Support GSI-191, " Westinghouse Electric Company (2008)] or formed in situ by injecting metal salts under two different rates (0.75 and 7.5 mL/min) were tested. The results show that the thin debris bed ( 10 mm) was more sensitive to the chemical precipitates prepared following the WCAP procedure compared to the intermediate debris bed ( 25 mm) and thick debris bed ( 55 mm). The measured chemical head loss was 0.35, 0.1, and 0.02 H2 O '' /mg of Al filtered by the debris beds. The in situ injection method has shown higher measured chemical head loss per unit mass of filtered precipitates than the WCAP surrogates for the debris beds of η = 2 (intermediate bed) and 1.15 (thick bed). Also, the results show a nonconclusive effect on the injection rate of metal salt to form in situ chemical precipitates on the measured chemical head loss.